Sustainable urban development and industrial pollution - Petrović, Julka J; Lečić, Dušanka; Pavlović, Dejan (Industrija, 2016)
Sustainable development of cities is highly connected with the pollution generated from industrial facilities and power plants. Both affect quality of air, weather, health and quality of life. The main goal of this paper is to determine the impact of selected weather parameters on the pollution from mentioned plants. From the research results, it can be concluded that sustainable urban development and welfare of citizens are dependent on causal relationship between pollution and weather. The greatest level of impact was recorded for nitric dioxide. In the case of carbon monoxide, the level of impact is the middle. The lowest level was recorded for particulate matter. The biggest impact on the carbon monoxide emission and particulate matter is that of air pressure, whereas temperature has the biggest impact on nitrogen dioxide emission. The research shows that air humidity and wind speed do not have a significant impact on the emission of pollutants from the plants. Research shows need for further studies in the field of impact of pollution from industry on urban weather and human health.
Keywords: Weather parameters; Industrial pollution; Urban development